Partial antagonism of propofol anaesthesia by physostigmine in rats is associated with potentiation of fast (80–200 Hz) oscillations in the thalamus - Reed, S.J.; Plourde, G.; Tobin, S.; Chapman, C.A. (British journal of anaesthesia : BJA, 2013)
Positron emission tomography studies in human subjects show that propofol-induced unconsciousness in humans is associated with a reduction in thalamic blood flow, suggesting that anaesthesia is associated with impairment of thalamic function. A recent study showed that antagonism of propofol-induced unconsciousness by the anticholinesterase physostigmine is associated with a marked increase in thalamic blood flow, supporting the implication of the thalamus. The aim of the present study was to assess the role of the thalamus in the antagonistic effects of physostigmine during propofol anaesthesia using electrophysiological recordings in a rat model. Local field potentials were recorded from the barrel cortex and ventroposteromedial thalamic nucleus in 10 chronically instrumented rats to measure spectral power in the gamma/high-gamma range (50–200 Hz). Propofol was given i.v. by target-controlled infusion at the lowest concentration required to abolish righting attempts. Physostigmine was given during anaesthesia to produce behavioural arousal without changing anaesthetic concentration. Compared with baseline, gamma/high-gamma power during anaesthesia was reduced by 31% in the cortex (P=0.006) and by 65% in the thalamus (P=0.006). Physostigmine given during anaesthesia increased gamma/high-gamma power in the thalamus by 60% (P=0.048) and caused behavioural arousal that correlated (P=0.0087) with the increase in power. Physostigmine caused no significant power change in the cortex. We conclude that partial antagonism of propofol anaesthesia by physostigmine is associated with an increase in thalamic activity reflected in gamma/high-gamma (50–200 Hz) power. These findings are consistent with the view that anaesthetic-induced unconsciousness is associated with impairment of thalamic function.